DESCRIPTION OF LEARNING MODEL BASED ON PROBLEM - Maku, Revalina; B. Jassin, Iwan (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
The Problem-Based Learning model is a process to enhance Problem-Solving and Critical Thinking Skills. This classroom action research aims to improve students' problem-solving and critical thinking skills by implementing the problem-based learning model. The research was conducted in two cycles, each consisting of planning, implementation, observation and evaluation, and reflection stages. The subjects of the study were students of the Educational Technology Department at FIPB class of 2025, totaling 9 students, who took the Learning and Teaching course. The object of the research was to observe students observing the learning process. The results obtained from this study show that the implementation of the problem-based learning model can enhance students' problem-solving and critical thinking skills. Students were very enthusiastic about participating in the learning and received the implementation of this learning model very well.